2003
DOI: 10.1021/ja035176q
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Molecule That Displays Context-Dependent Cellular Activity

Abstract: The cell-permeable dihydrofolate reductase inhibitor methotrexate was covalently linked to a ligand for the protein FKBP to create a bifunctional molecule called MTXSLF. The covalent tether between the two ligands was designed to be prohibitively short, so that unfavorable protein-protein interactions between DHFR and FKBP preclude formation of a trimeric complex. In vitro and in vivo experiments demonstrate that MTXSLF is an effective inhibitor of human DHFR, but that efficacy is decreased in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 31 publications
1
46
0
2
Order By: Relevance
“…We have evaluated the effects of low dose (10 g/kg body weight) rapamycin and SLF (1 g/kg body weight) on skeletal muscle function and compare the drug effects with a skeletal muscle-specific deficiency in FKBP12. SLF does not alter mTORC1 or calcineurin activity (22). We demonstrate that rapamycin, SLF, and muscle-specific deficiency in FKBP12 enhance the refilling of SR Ca 2ϩ stores, turn on the slow fibertype program, slow muscle fatigue, and improve running endurance in mice.…”
mentioning
confidence: 76%
“…We have evaluated the effects of low dose (10 g/kg body weight) rapamycin and SLF (1 g/kg body weight) on skeletal muscle function and compare the drug effects with a skeletal muscle-specific deficiency in FKBP12. SLF does not alter mTORC1 or calcineurin activity (22). We demonstrate that rapamycin, SLF, and muscle-specific deficiency in FKBP12 enhance the refilling of SR Ca 2ϩ stores, turn on the slow fibertype program, slow muscle fatigue, and improve running endurance in mice.…”
mentioning
confidence: 76%
“…The high affinity and specificity of this protein-ligand interaction suggested that it might be used to label proteins with chemical conjugates to SLFЈ. Because dimeric forms of synthetic ligands for FKBPs retain high affinities, we reasoned that conjugation of fluorescent dyes or other small molecules to the same site would not affect binding (16,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the combination of FKBP and the bifunctional molecule also blocked formation of toxic A oligomers, suggesting that this general approach might lead to compounds that can reduce the toxicity of amyloids. These studies, along with others in which FKBP has been chemically co-opted [101,102], demonstrate how a protein can synthetically acquire new functions. In the discussed example, the new protein-protein interaction between FKBP and A (enforced by the synthetic compound) endows the FKBP with a new capability: inhibition of amyloid formation.…”
Section: Creating New Protein Functionsmentioning
confidence: 79%